Global Satellite Meteorological Observation (GSMO) Applications Volume 2 - Ilčev, Stojče Dimov; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents principal structures of space systems functionality of meteorological networks, media and applications for modern remote sensing, transmission systems, meteorological ground and users segments and transferring weather data from satellite to the ground infrastructures and users. The author presents techniques and different modes of satellite image interpretation, type of satellite imagery, spectral imaging properties, and enhancement of imaging technique, geo-location and calibration, atmospheric and surface phenomena. Several satellite meteorological applications are introduced including common satellite remote sensing applications, weather analysis, warnings and prediction, observation and measurements of meteorological variables, atmosphere and surface applications, ocean and coastal applications, land, agriculture and forestry applications, and maritime and aviation satellite weather applications. The author also covers ground segment and user segment in detail. The final chapter looks to the future, covering possible space integrations in meteorological and weather observation.This is a companion book of Global Satellite Meteorological Observation Theory (Springer), which provides the following topics: Evolution of meteorological observations and history satellite meteorology Space segment with satellite orbits and meteorological payloads Analog and digital transmission, type of modulations and broadcasting systems Atmospheric radiation, satellite meteorological parameters and instruments Meteorological antenna systems and propagation.
Introduction -- Space Segment -- Baseband and Transmission Systems -- Atmospheric Electromagnetic Radiation -- Satellite Meteorological Parameters -- Satellite Meteorological Instruments -- Antenna Systems and Propagation. Conclusion.
Keywords: Telecommunication; Electronics; Transportation engineering; Traffic engineering; Computer networks .; Law of the sea; International law; Aeronautics -- Law and legislation; Communications Engineering, Networks; Electronics and Microelectronics, Instrumentation; Transportation Technology and Traffic Engineering; Computer Communication Networks; Law of the Sea, Air and Outer Space